Commercial cannabis product testing: Fidelity to labels and regulations - Sarah A. Limbacher; Suneeta Godbole; Julia Wrobel; Duncan I. Mackie; Stephen Goldman; Ashley Brooks-Russell (PLoS ONE, 2026)
Background In Colorado, regulations for recreational and medical cannabis sales require tetrahydrocannabinol (THC) concentration is printed on all products. Labeled THC concentrations can vary by +/-15% of what is in the product. Studies show THC concentrations recorded on product labels are not always reflective of the THC concentration in the cannabis product and there is evidence consumers make purchasing decisions based on label claims. Aims Explore the accuracy of cannabis product labels and differences between THC label accuracy and product type. Design Data for this analysis come from a larger observational study of cannabis impairment. N = 74 flower, concentrate, and edible product samples from licensed Colorado dispensaries were collected and independently tested for THC concentration. Setting This study was conducted in Colorado, in the Denver Metro Area. Participants Participants in the study voluntarily enrolled and provided one-gram samples of the cannabis they consumed during the study to be independently tested. The cannabis tested for this analysis was donated on a voluntary basis, not all participants chose to donate. Measurement The main outcomes of interest for this analysis are accuracy of cannabis product labels compared to observed THC content, accuracy in the context of legally allowable variation, and difference between accuracy by product. Findings Overall, label values were higher than observed values in flower and edible products (p < 0.001) but was not significant for concentrates (p = 0.85). Flower products were observed to be significantly lower on labels versus the 15% legally allowable range (p = 0.04). Concentrate and edible products were not significantly different (p = 0.9 and p = 0.5, respectively). Conclusions There is tension between legally allowable THC concentration claims on cannabis product labels and how consumers purchase cannabis. As cannabis policy evolves, standards and regulations that ensure accurate THC concentrations are reported on product labels are urgently needed.